Adding a nutrition behavior change communication component to an early childhood development intervention in Malawi: A cluster randomized trial - Gelli, Aulo; Gladstone, Melissa; Twalibu, Aisha; Nnensa, Theresa; Kariger, Patricia; Alderman, Harold (International Food Policy Research Institute, 2019)
The Nutrition Embedded Evaluation Program Impact Evaluation (NEEP-IE) cluster randomized control trial (CRCT) aimed to assess the effectiveness of implementing an agriculture and nutritional intervention through preschools, known as community-based child care centres (CBCCs) in Malawi (6). This included; activities to promote nutritious food production and consumption, promotion of optimal feeding and caring practices and engagement with parents in pre-school meal planning and preparation. The NEEP-IE trial has demonstrated that CBCCs can be an effective platform to scale-up an integrated agriculture and nutrition intervention, and improve food production diversity, maternal knowledge, nutrition practices at household level and diets of pre-schoolers and their younger siblings, as well as improve linear growth in younger siblings aged 6-24m (7). This study presents the impact results of the NEEP-IE trial focusing on child development outcomes of pre-school children during a 12m intervention period.